Atypical presentation of metoclopramide‐induced galactorrhea. (December 2015) - Menon, Parvathy; Thunga, Girish; Nambiar, Srikanth; Khera, Kanav
Abstract: Background: Metoclopramide is commonly used for the management of nausea and vomiting, but is associated with a range of adverse effects, including galactorrhea. Aim: To present a case of an atypical presentation of metoclopramide‐induced galactorrhea. Clinical details: A previously asymptomatic 30‐year‐old woman was treated with metoclopramide for management of gastrointestinal symptoms. Five days after the initiation of treatment she developed pain in both breasts and whitish discharge from nipples of both breasts, which was subsequently identified as milk. Her last menstrual period was 4 days before admission to hospital, and had lasted only for a day. Four years prior to admission, she had undergone a tubectomy. Transvaginal ultrasound was used to rule out pregnancy. Thyroid, liver and kidney function were normal, and the serum concentration of prolactin at this time was 1.8 ng/mL (reference range 3.3–26 ng/mL), slightly below the normal level. Metoclopramide was discontinued and galactorrhea, mastalgia and fever subsided. Outcomes: Metoclopramide was discontinued and galactorrhea, mastalgia and fever subsided. Conclusion: Although previous reports have described metoclopramide‐induced galactorrhea in association with hyperprolactinaemia, this case appears to represent a probable atypical presentation of an adverse drug reaction.